2011
DOI: 10.1152/ajpregu.00398.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid and GABA modulation of sympathetic nerve activity and blood pressure in the dorsal periaqueductal gray of the rat

Abstract: Sympathoexcitation and increased blood pressure evoked by central networks integrating defensive behavior are fundamental to the acute stress response. A balance between excitatory glutamatergic and inhibitory GABAergic neurotransmission in the dorsal periaqueductal gray (dPAG) results in a tonic level of activity in the alerting system. Neuromodulators such as endocannabinoids have been shown to influence the sympathoexcitatory and pressor components of acute stress in the dPAG, exemplified by the defense res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
(52 reference statements)
1
28
0
Order By: Relevance
“…Mobilization of ECS in the rat dorsal periaqueductal gray (PAG) enhances SNS activation [113, 114]. CB1R are found in the PAG [115] and microinjection of AEA into the dorsal PAG increases renal sympathetic nerve activity within 30 sec of injection [113].…”
Section: Ecs and Sympathetic Nervous System Responses To Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobilization of ECS in the rat dorsal periaqueductal gray (PAG) enhances SNS activation [113, 114]. CB1R are found in the PAG [115] and microinjection of AEA into the dorsal PAG increases renal sympathetic nerve activity within 30 sec of injection [113].…”
Section: Ecs and Sympathetic Nervous System Responses To Stressmentioning
confidence: 99%
“…CB1R are found in the PAG [115] and microinjection of AEA into the dorsal PAG increases renal sympathetic nerve activity within 30 sec of injection [113]. These effects are inhibited by CB1R antagonist pretreatment and are consistent with CB1R-mediated inhibition of GABA release [114]. Microinjection of CB1R antagonist into the dorsal PAG also inhibits SNS responses evoked by hypothalamic stimulation [113].…”
Section: Ecs and Sympathetic Nervous System Responses To Stressmentioning
confidence: 99%
“…While endocannabinoid modulation of sympathetic outflow is associated with stress responses in the dPAG, (12, 13), it is not known whether endocannabinoids in this midbrain region contribute to ongoing sympathetic tone through this circuitry, Therefore, the present study was undertaken to determine whether endocannabinoid signaling in the dPAG contributes to autonomic and cardiovascular regulation under resting conditions.…”
mentioning
confidence: 99%
“…Cannabinoids can enhance autonomic activity and cardiovascular parameters through endocannabinoid signaling in the dorsal periaqueductal gray (dPAG), a highly integrative region, the activation of which is associated with enhanced sympathetic and cardiovascular regulation in emotional behaviors (28). Endocannabinoids function in the dPAG by inhibiting tonically active GABAergic neurons to exert a profound activation of output neurons, leading to an increase in sympathetic nerve activity and blood pressure (12, 13). …”
mentioning
confidence: 99%
“…There are previous studies showing that either electrical or chemical stimulation with the broad-spectrum excitatory amino acid dl-homocysteic acid (DLH) or glutamate (200 nL) or NMDA (200 nL) in the dPAG induce a panic-related defensive response and/or anxiety-like behavior in animals (Ballesteros et al, 2014;Camplesi et al, 2012;de Almeida et al, 2006;Dean, 2011;Krieger and Graeff, 1985;Reimer et al, 2012). However, another set of studies have demonstrated that there is a behavior-related distinction between columns of the PAG, suggesting that the lateral and dorsolateral (dlPAG) regions (Bandler and Shipley, 1994;Bandler et al, 2000;Carrive, 1993;da Silva et al, 2006) are associated with behavioral reactions, while the dorsomedial region (dmPAG) is not (Pelosi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%